The Effect of Person-Job Fit on Turnover Intention: Mediated by Job Satisfaction - Yugi Adhari Nugraha (IJHCM (International Journal of Human Capital Management), 2021)
Abstract Background: In the banking industry, employees have an important role in the success and stability of the company in facing challenges, competition, and employee mobility.. Objective: aims to analyze the effect of person-job fit and job satisfaction on employee turnover intention. Authenticity/Value: The novelty of this research is because there are still few who pay attention to the problem of the influence of persob-job fit on turnover intention for the sustainability of the bank. Limitations: The research problem is limited to the effect of person-job fit and job satisfaction on employee turnover intention. Methodology/ Approach: This research was conducted with a sample unit taken from 54 employees. Research data obtained by distributing questionnaires were analyzed using the SEM-PLS method. Findings: The results showed that there was an effect of person-job fit on job satisfaction. There is an effect of job satisfaction on turnover intention. There is no effect of person-job fit on employee turnover intention.